Social Vulnerability of Productive Age Groups to Post-Pandemic Economic Uncertainty: A Regional-Based Socio-Economic Analysis → Employment and Inequality Issues - Ika Rahma (Archipel: Journal of Indonesian Interdisciplinary Studies, 2025)
This study explores the social vulnerability of productive-age groups to post-pandemic economic uncertainty through a comprehensive literature review. The study's primary focus is on labor dynamics, regional inequality, and the structural impacts of labor market changes following the COVID-19 pandemic. Through a systematic review of recent scientific publications and empirical reports, the study identifies vulnerability patterns associated with job insecurity, the vulnerability of informal workers, and differences in experiences across regions. Findings indicate that productive-age groups experience multidimensional vulnerability rooted in job instability, limited social protection, and disparities in access to employment opportunities influenced by regional characteristics. The literature also highlights how pre-pandemic inequalities contribute to differential impacts across demographic groups, including urban versus rural populations. The synthesis of findings demonstrates the need for adaptive labor policies and more inclusive social protection to mitigate this vulnerability. This study emphasizes that understanding social vulnerability must consider the interplay of economic and geospatial factors to support policy formulation responsive to post-pandemic realities.